Experimental Study on Brush-Painted Passive RFID-Based Humidity Sensors Embedded into Plywood Structures - Erja Sipilä; Johanna Virkki; Lauri Sydänheimo; Leena Ukkonen (International Journal of Antennas and Propagation)
The integration of electronics and wood is an interesting research area due to the increasing interest to add functionality into various wooden products. The passive RFID-based humidity sensor tag prototype, presented in this paper, is fabricated directly on plywood substrate to be embedded into wooden structures, by using brush-painting and photonic sintering of cost-effective silver ink. To the best of our knowledge, this is the first demonstration of brush-painted antennas as sensor elements. The developed sensor tag is fully passive and small in size, meaning it can be permanently enclosed into wooden structures. In addition, the sensor tag has all the functionalities of an ordinary passive UHF RFID tag, and a peak read range of about 10 meters. The sensor performance was evaluated in normal room conditions, after two 100% relative humidity tests, and after drying in normal room conditions for 9 days. According to the results, the fabricated UHF RFID-based humidity sensor tags have a great potential to be utilized in humidity sensing applications, and also in normal automatic identification and supply chain control of various wooden products. In addition, the first results of more cost-effective brush-painted copper UHF RFID tags on plywood substrate are presented.